2018
DOI: 10.1093/bioinformatics/bty1032
|View full text |Cite
|
Sign up to set email alerts
|

Very low-depth whole-genome sequencing in complex trait association studies

Abstract: Motivation Very low-depth sequencing has been proposed as a cost-effective approach to capture low-frequency and rare variation in complex trait association studies. However, a full characterization of the genotype quality and association power for very low-depth sequencing designs is still lacking. Results We perform cohort-wide whole-genome sequencing (WGS) at low depth in 1239 individuals (990 at 1× depth and 249 at 4× dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…The lack of supporting resources for diverse ancestries creates financial challenges for association studies with limited resources, e.g. raising questions about whether to genotype samples on GWAS arrays that may favor European allele frequencies versus sequence samples, and how dense of an array to choose or how deeply to sequence 71,72 .…”
Section: How Do We Even the Ledger?mentioning
confidence: 99%
“…The lack of supporting resources for diverse ancestries creates financial challenges for association studies with limited resources, e.g. raising questions about whether to genotype samples on GWAS arrays that may favor European allele frequencies versus sequence samples, and how dense of an array to choose or how deeply to sequence 71,72 .…”
Section: How Do We Even the Ledger?mentioning
confidence: 99%
“…We employ several strategies which account for these effects and do not require knowledge of the specific causal variants to quantify the extent to which genetic variants affecting lipid biomarkers are shared between individuals from Europe/North America, Asia, and Africa. We assess the transferability of individual signals and compare association patterns across the genome using data from the African Partnership for Chronic Disease Research – Uganda (APCDR-Uganda, N = 6407) 8 , China Kadoorie Biobank (CKB, N = 21,295) 9 , the Hellenic Isolated Cohorts (HELIC-MANOLIS, N = 1641 and HELIC-Pomak, N = 1945) 10,11 , and the UK Household Longitudinal Study (UKHLS, N = 9961) 12 . We also use summary statistics from Biobank Japan (BBJ, N = 162,255) 13 and the Global Lipid Genetics Consortium (European ancestry, GLGC2013 N = 188,577, GLGC2017 N = 237,050) 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Although our sample size was smaller for GWAS, the variants with high frequency and large effect have been identified, and further GWAS with a larger sample size will result in the identification of additional variants with low frequency and small effect in future. In addition, our genome coverage was very low (∼5.60×), but a previous study has shown that very low-depth whole-genome sequencing is an efficient alternative to complex trait association studies (Schwartzentruber et al, 2018).…”
Section: Discussionmentioning
confidence: 98%